1973
DOI: 10.1073/pnas.70.2.401
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for 30-40S RNA as Precursor of the 60-70S RNA of Rous Sarcoma Virus

Abstract: Rous sarcoma virus harvested from cells at intervals of 3 min has the same density, sedimentation coefficient, and DNA polymerase as virus harvested at hourly intervals. The RNA of the Prague strain-C consists of a minor class of 60-70 S RNA, a major class 30-40 S RNA, and a 4-12 S class of RNA present at variable concentration. The RNA of the Schmidt-Ruppin strain-A contains more 60-70S than 30-40S RNA. Upon incubation of virus harvested at 3-min intervals at 400 in cell growth medium or Trissaline, most of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
66
0

Year Published

1974
1974
2001
2001

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(72 citation statements)
references
References 19 publications
6
66
0
Order By: Relevance
“…The network structure we observe for the 60-70S RNA is consistent with the following earlier observations (21)(22)(23)(24): Virus collected at 12-to 24-hr intervals yields a 60-70S RNA peak that is very similar to that obtained from virus collected at 3-to 5-hr intervals. Heating the 60-70S RNA of 12-to 24-hr virus, however, results in a wide distribution of molecules sedimenting between zero and 40 S; whereas heating the 60-70S RNA of virus collected at 3-to 5-hr intervals yields a relatively sharp peak of 30-40S RNA.…”
Section: Methodssupporting
confidence: 76%
“…The network structure we observe for the 60-70S RNA is consistent with the following earlier observations (21)(22)(23)(24): Virus collected at 12-to 24-hr intervals yields a 60-70S RNA peak that is very similar to that obtained from virus collected at 3-to 5-hr intervals. Heating the 60-70S RNA of 12-to 24-hr virus, however, results in a wide distribution of molecules sedimenting between zero and 40 S; whereas heating the 60-70S RNA of virus collected at 3-to 5-hr intervals yields a relatively sharp peak of 30-40S RNA.…”
Section: Methodssupporting
confidence: 76%
“…It was recently shown that considerable conformational changes occur in the RNA of extracellular RSV during hours of contact with the cells; RSV RNA, separated from the cells at 3-min intervals, was 30-35 S without heating, and formed the 70S component only secondarily (18). It appeared to us that terminal dephosphorylation might also take place during the customary hours of incubation of released virus in the presence of cells and their medium, and that different results might be obtained if virus for end-group analysis was also collected at 3-min intervals.…”
Section: Resultsmentioning
confidence: 99%
“…The 30-35S RNA used was obtained by heating viral RNAs at 1000 for 45 sec, followed by another sucrose gradient fractionation. The RNA, together with carrier RNA of tobacco mosaic virus (TMIV) used as a 30S marker on sucrose gradients, was hydrolyzed in 50,ul of 0.3 M KOH for 18 hr at 370 in a sealed capillary tube, and then spotted directly with absorbance markers (nucleosides and nucleotides) 44.5 cm from the anode side, and 8 cm from one edge of a sheet of Whatman 3 MM paper of 95 X 48 cm. Electrophoresis was in a refrigerated two-phase electrophoresis system, with pyridine-acetate buffer at pH 3.5 (5% v/v glacial acetic acid, 0.5% v/v pyridine, and 1 mM EDTA) at about 3000 V for 4 hr.…”
mentioning
confidence: 99%
“…Stocks of vPN-1 and vPN-2 (virus harvested from VOL. 5,1985 on May 11, 2018 by guest http://mcb.asm.org/ Downloaded from cells containing pPN-1 and pPN-2 sequences, respectively) were recovered from transfected cells as RAV-1 pseudotypes after four cell passages; the delay between transfection and harvest allowed the cultures to become fully infected.…”
Section: Kbmentioning
confidence: 99%